Time-varying granger causality tests for applications in global crude oil markets: A study on the DCC-MGARCH Hong test - Massimiliano Caporina; Michele Costola (Leibniz Institute for Financial Research SAFE, 2021)
Analysing causality among oil prices and, in general, among financial and economic variables is of central relevance in applied economics studies. The recent contribution of Lu et al. (2014) proposes a novel test for causality- the DCC-MGARCH Hong test. We show that the critical values of the test statistic must be evaluated through simulations, thereby challenging the evidence in papers adopting the DCC-MGARCH Hong test. We also note that rolling Hong tests represent a more viable solution in the presence of short-lived causality periods.
urn:nbn:de:hebis:30:3-616382
Keywords: C10; C13; C32; C58; Q43; Q47; 330; Granger Causality; Hong test; DCC-GARCH; Oil market; COVID-19